Use of cognitive techniques is associated with change in positive compensatory skills in the treatment of major depressive disorder in a community mental health setting. (3rd October 2021) - Crits-Christoph, Paul; King, Catherine; Goldstein, Elena; Connolly Gibbons, Mary Beth
Abstract: Objective: : To examine the association between adherence and competence in cognitive therapy (CT) techniques and change in positive compensatory skills and depressive symptoms within a community mental health setting. Method: : Adherence ratings were available for 97 individuals receiving CT for major depressive disorder. Assessments of adherence and competence were rated on one early session of CT. Compensatory skills were measured using the Ways of Responding Community Version at baseline and months 1, 2, and 5. Symptom severity was evaluated using the Hamilton Rating Scale for Depression at baseline and months 1, 2, 4, and 5. Results: : In mixed effects models, adherence was significantly associated with linear change in positive compensatory skills from baseline to month 5 ( F [1, 76] = 8.05, p =.006, r =.31). Competence was also significantly associated with change in positive compensatory skills from baseline to month 5 (F [1, 78] = 5.1, p=.027, r=.25). High adherence was associated with improvements in HAM-D scores from baseline to month 5 (F [1, 78] = 5.1, p=.027, r=.25). Conclusions: : Results support the hypothesis that use of CT techniques is associated with change in compensatory skills in a community mental health setting.